Catch crops for forage and green manure - Gripton, David H. (My University, 1906)
Introduction: By the term catch crops is commonly understood a crop which is used to occupy the soil at a time when it would otherwise be vacant, whether this vacancy is caused by the failure of one of the regular crops of the farm or coming between the time of harvesting one crop and the planting of the succeeding one. The catch crop occupies a field which in the more common farm practice would remain bare or unproductive during the interval of the growing of the crop. It is often an emergency crop, that is a crop not at first planned for but introduced to supply a want which is a consequence of an accident or unforseen conditions. A rigid regard for the teachings of farm economy would make "catch crops," as regular members of our rotation as any of the crops of the farm. It is not more true that "Nature abhors a vacuum" than that the good farmer abhors a bare field. The increased labor in the care of crops in subsequent years resulting from the germination of the countless weed seed developed in the idle field, will make heavy inroads upon the owner's time and money. The catch crop may be made to keep down these weeds and at the same time improve the mechanical condition of the soil; and these are two of the chief advantages of growing catch crops. The catch crop feeds on food material which is made soluble and thus retains it for use in the next crop, where it might otherwise be leached away. A catch crop, in so far as possible, should combine the following characteristics: cheap seed; rapid growth; ability to thrive when so broadcast; freedom from characters, either of root or seed, which will cause it to become a troublesome weed; a deep vigorous root system; the ability to take part of its nitrogen from the air; hardiness; ability to stand frost and to grow at a low temperature; and to be of value either for forage or for soil improvement.
Citation: Gripton, David H. Catch crops for forage and green manure. Senior thesis, Kansas State Agricultural College, 1906.
Morse Department of Special Collections
Keywords: Agriculture; Catch Crops; Forage; Green Manure; Theses